Analysis of Using Picture to Improve Students’ Writing Skill of Descriptive Text - Novi Rahayu (English Instruction, 2020)
This study aimed to find out the effect of using picture to improving student’s writing skill of descriptive text by applying Descriptive Qualitative research with literature studies. In this study, researcher using a literature study by looking for several related sources on the internet to be analyzed so that the instrument in this study is the researcher themselves. In collecting data from several related sources which are then analyzed related to student weaknesses in writing and the effect of using pictures after being applied in teaching writing as a teaching technique. The difficulty faced by students in writing is in finding references and writing techniques, besides that there are also weaknesses in analyzing vocabulary and also grammatical structures. This is why plagiarism is still very high. There are several factors that cause difficulty in writing including low reading interest, low curiosity, low motivation in writing, and unclear writing methods. The results showed some changes and positive responses from students. Thus, pictures have a significant effect on students' skill in writing descriptive text. The increase in students' skill in writing is due to using pictures, students become more interested and not bored to listen to the teacher's explanation so that they are more active in the classroom.